Hermeneutics of Schleiermacher, Dilthey, Heidegger and Gadamer on Financial Statements in the Indonesia Stock Exchange (2010–2024) - Apollo, Apollo; Hariani, Swarmilah; Herliansyah, Yudhi (DINASTI RESEARCH, 2025)
This study investigates the interpretive and philosophical dimensions of financial reporting practices on the Indonesia Stock Exchange (IDX) from 2010 to 2024, through the lens of classical and contemporary hermeneutics. Rooted in the traditions of Friedrich Schleiermacher, Wilhelm Dilthey, Martin Heidegger, and Hans-Georg Gadamer, this research reinterprets financial reports particularly annual and sustainability disclosures not as neutral, technical documents, but as culturally embedded, historically conditioned texts. These documents are viewed as expressions of corporate subjectivity and intersubjective engagement with stakeholders, regulators, and the public. The research adopts a qualitative interpretive methodology, emphasizing textual exegesis over empirical generalization. Drawing on the hermeneutic principles of pre-understanding, historicality, and the fusion of horizons, this paper performs a layered reading of selected financial statements from Indonesian public companies across multiple sectors. The study highlights how financial narratives evolve in language, structure, tone, and ethical framing over time. The novelty of this research lies in the formulation of a new conceptual framework: Narrative Legitimacy Construction Theory (NLCT). NLCT posits that financial reporting is not merely about compliance or representation, but a dynamic narrative strategy used by firms to construct legitimacy in fluctuating political-economic environments. This theory integrates hermeneutic phenomenology with semiotic accounting, showing how meaning-making in financial texts reflects deeper ontological claims about value, risk, time, and responsibility. The findings reveal a shift from mechanistic, number-driven disclosure to ethically resonant narratives, particularly after the implementation of digital transparency frameworks and sustainability mandates. Companies strategically deploy metaphors, temporal references, and identity claims to construct a coherent and persuasive corporate image. This research contributes to the development of post-positivist accounting thought, expands the hermeneutic approach to financial analysis, and informs practitioners and regulators about the embedded ethical and narrative dimensions of financial communication.